PENGARUH LATIHAN SENAM AEROBIK â€œLOW INTENSITYâ€ SELAMA 1 (SATU) JAM TERHADAP PENURUNAN GLUKOSA DALAM DARAH PADA ANGGOTA SANGGAR SENAM PUSKESMAS KAMPAR KIRI TENGAH DESA SIMALINYANG KECAMATAN KAMPAR KIRI TENGAH KABUPATEN KAMPAR - Tonamal, Toni; Juita, Ardiah; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Based on the observation that researchers do in local goverment clinicMiddle East Kampar of the interview, the researcher found the reason they followed thegymnasium to practice at the same time maintaining the health of the disease whichavoid one diabetes and obsitas. The aim of this study was to investigate the effect ofaerobic exercise